Small-Cell Lung Carcinoma Associated With Cystic Airspaces: A Case Report - Hirokazu Touge; Haruki Masui; Mitsuhiro Yamamoto; Tomoyuki Ikeuchi; Tomohiro Sakamoto; Katsuyuki Tomita; Akira Yamasaki (Case Reports in Medicine, 2025)
Small-cell lung carcinoma (SCLC) associated with cystic airspaces is rare. We describe the case of a 68-year-old man who was referred to our hospital because of a cystic lesion detected on chest radiography. Initial computed tomography revealed a small nodule abutting the cystic airspace due to paraseptal emphysema in the right lower lobe. Histopathological examination of lymphadenopathy indicated SCLC. Postchemotherapy, recurrence appeared as a thick-walled cystic airspace with an exophytic nodule along the cyst wall, mimicking pneumonia. Additional chemotherapy, but not antibiotic therapy, led to a reduction in the wall thickness and nodules. This case emphasizes unresponsiveness to antibiotic therapy, especially in patients with risk factors, highlighting the diagnostic pitfall that may delay timely cancer treatment.